Developing solid engine for green energy harvesting - Lim, Terence Hiap Teng (2014)
The project requires two members, one from design stream and one from other specialisation, to work together to develop the prototype. The scope will include design, materials evaluation, fabrication, prototype demonstration and evaluation. One student will focus on the design and the other will focus on the smart materials issues. Both will need to collaborate to design and fabricate the prototype together and to evaluate its workability and efficiency.